(3fRgI GdCUMGH aj eYGTQI GdCMHGHs - (3CHh fUQ GdSehCd Hf jMji Hf YHGS GdeZQHj GdGSQGFjdj,J (B570 (3g` s ((3eMeO Hf CMeO GHf YKeGf GdTGaYi s)
(3ChdgG (B:s
(3agh GdPi jOYi ajLjH hjMUd Pdc Ydi faSg efg HGdhaGA , Ke jJKGbd Yf GdOGYi Gdedgha MJi jLjHg s
(3BNQgG (B:s
(3hCSJZaQ Gddg eeG jMHW GdYed dOjg , hCSJhabg deG jbQH Gdjg s
(3YdjgG Jedc SfI (B868(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
GAL - (3GdLRA (B1 - (3U (B488 ; GAL - (3GdLRA (B1 - (3U (B692 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B275 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B273 s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(830) s
Keywords: (3GdWHs